Dietary Diversity and Associated Factors among HIV Positive Adult Patients Attending Public Health Facilities in Motta Town, East Gojjam Zone, Northwest Ethiopia, 2017 - Addisu Tesfaw; Dube Jara; Habtamu Temesgen (Hindawi Limited, 2018)
Introduction. Dietary diversity is defined as the amount of different food groups or foods that are consumed over a specific reference time. The human immune deficiency virus problem remains one of the main public health challenges, especially in low and middle income countries. Nutrition has been linked to both the transmission of human immune deficiency virus and poor outcomes related to human immune deficiency virus. Objective. To assess dietary diversity and associated factors among human immune deficiency virus positive adult patients in Motta administrative town, Northwest Ethiopia, 2017. Methods. A facility based cross-sectional study design was conducted on 410 study participants selected using a stratified sampling technique with proportional allocation. The data were collected using semi-structured and pretested questionnaire. Data were entered into Epi-Data version 3.1 and analysis was performed using SPSS version 20. Descriptive statistics were used to describe the number and percentage of the study variables. The bivariate and multivariable logistic regression analyses were done to identify the independent factors associated with dietary diversity among adult human immune virus (HIV) positive patients. Result. A total of 410 study participants were included in the analysis. Of the total, 121 (29.5%) of adult HIV positive respondents consumed diversified diet with the mean dietary diversity score of 3.2 (SD±1.88). The predominant food item consumed during the study periods was starchy staples (96.1%) and legumes (81.7%). Having means of communication cell phone (mobile phone) [(AOR= 2.13 (1.16, 3.60)], media exposure status in the household [(AOR =1.95 (1.22, 3.11)] and nutrition counselling [(AOR =2.17 (1.09, 4.67)] were significant factors associated with dietary diversified feeding at 95% CI. Conclusion. The study revealed that low dietary diversity score was significant nutritional problem among HIV positive adults in Motta town health facilities. Having mobile cell phone, media exposure status and nutritional counseling were significantly associated with dietary diversity score. Therefore efforts should be strengthened to improve the counseling service at each health institution and encourage the patients to use media for the source of information.